Perception and readiness of community pharmacists on the use of mobile smart phone as a health monitoring tool - Pei Lin, Lua; Umar Idris, Ibrahim (2015)
The use of communication technology has brought positive changes to the healthcare delivery system of today. Both healthcare professionals and patients have found a better option to access relevant health and drug information. The purpose of this review is to compile and evaluate all available investigations on the application of communication technology in hospital and community pharmacies. Pub Med, Medline and EBSCO host databases were searched using the key words: mobile phone, pharmacy and telecommunication, pharmacy and electronics, electronic record in pharmacy from the year 1994 until August 2014; whereby only full length English articles related to the review were included. Ten studies met all inclusion criteria comprising of 1124 respondents (age = 19-63, males=43%). Majority of the studies were cross-sectional in nature. Six utilized mobile phones as their means of communication of which majority (n=5) utilized text messages. Four utilized computer systems as their means of communication where they mostly work on drug-drug interaction software. Most of the reviewed studies demonstrated that incorporation of information technology in pharmaceutical care delivery and pharmacy training has improved patient satisfaction and produced better outcomes. However, several studies indicated that drug-drug interaction software had increased burden on the pharmacy staff and in some cases caused the distraction. Overall, there were positive reports on the use of communication technology which was found to help in improving pharmaceutical care.